Just transition for workers during environmental change (Winnipeg, 2000)
"The labour movement's vision of a healthy Canadian environment is founded on sustainability - a sustainable economy, sustainable employment, sustainable production and the public services that support it: a future for all Canadian in a sustainable society. All these modes of sustainability embody the idea of durability: long-lasting quality jobs; production processes that are safe, healthy and stress-free; and durable products, in a social environment that will not succumb to resource exhaustion, gross pollution, non-renewable energy sources and endemic waste. This vision requires workers' participation and control over our own future. Otherwise, any environmental change will be incomplete and one-sided; it will benefit only the rich and privileged. Just Transition is essential to the process of environmental change. Many of our members work in jobs that will become obsolete if unsustainable production, environmental degradation and resource exhaustion are allowed to continue along their current path. But if workers' health and livelihoods in high-paying quality jobs are to be secured, there will have to be safeguards so that workers are not simply thrown on the scrap heap as a sustainable economy, in both the manufacturing and service sectors, takes the place of unsustainable modes of production. The labour movement has a vital role, not only in working for Just Transition, but in following up the moves to sustainability, so that displaced workers continue to work in a union environment, with all the benefits and protections that unions have offered in the past. Just Transition is such a safeguard. It provides a measure of workers' participation and control over our own future. It is a building block for a sustainable economy, one essential element in a progressive environmental policy.